2015
DOI: 10.1111/nph.13757
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of sodium and chloride to assist breeding for salinity tolerance in crops

Abstract: SummaryThe separation of toxic effects of sodium (Na + ) and chloride (Cl À ) by the current methods of mixed salts and subsequent determination of their relevance to breeding has been problematic. We report a novel method (Na + humate) to study the ionic effects of Na + toxicity without interference from Cl À , and ionic and osmotic effects when combined with salinity (NaCl).Three cereal species (Hordeum vulgare, Triticum aestivum and Triticum turgidum ssp. durum with and without the Na + exclusion gene Nax2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 80 publications
4
68
0
4
Order By: Relevance
“…Salinity may cause osmotic stress, ionic toxicity through osmotic and biochemical processes and nutritional imbalances through reduced uptake of essential elements [1416]. Considerable fundamental knowledge has been gained in plant biology under salt stressed conditions at cellular and tissues level [15, 17, 18]. However, to our knowledge, new salt tolerant varieties have yet to be adopted following the targeting of specific physiological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity may cause osmotic stress, ionic toxicity through osmotic and biochemical processes and nutritional imbalances through reduced uptake of essential elements [1416]. Considerable fundamental knowledge has been gained in plant biology under salt stressed conditions at cellular and tissues level [15, 17, 18]. However, to our knowledge, new salt tolerant varieties have yet to be adopted following the targeting of specific physiological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the ability of shoot Na + exclusion was previously reported to be particularly crucial for crop salt tolerance (Tester and Davenport, 2003; Läuchli et al, 2008). However, Genc et al (2015) suggested that Na + exclusion is unlikely to be the main mechanism for crop salt resistance because a genetically modified wheat plant equipped with Na + exclusion genes did not show higher yields under salinity. In the present study, varieties with higher biomass (Hindmarsh, Vlamingh, and Sahara) also maintained lower Na + levels in shoots after salinity stress compared with varieties that were more sensitive to salinity (Clipper, Flagship, and Mundah) ( Table 3 , Supplementary Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The third aim of this study was to identify ion-specific effects by a comparative metabolite analysis; such effects are otherwise difficult to identify (Genc, Oldach, Taylor, & Lyons, 2016;Genc, Taylor, Rongala, & Oldach, 2014). We assume that if one metabolite increased in two salt treatments that shared the Na + ion (e.g., NaCl and Na 2 SO 4 ) but not in the third salt (i.e., KCl), then this effect is probably caused by Na + .…”
Section: Effects Of Single Ionsmentioning
confidence: 99%